2020
DOI: 10.1002/lary.28602
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging With Positron Emission Tomography/Computed Tomography and Magnetic Resonance Imaging to Detect Extracapsular Extension in Head and Neck Cancer

Abstract: Objectives/Hypothesis To assess the ability of specific positron emission tomography/computed tomography (PET/CT) and magnetic resonance imaging (MRI) features to detect extracapsular extension (ECE) in head and neck squamous cell carcinoma (HNSCC) patients. Study Design Retrospective study in a tertiary certified university cancer institute. Methods We performed a review of patients with advanced HNSCC at Bern University Hospital between 2014 and 2018. Patients with pretherapeutic PET/CT and/or MRI who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Features such as ECE were added in the last UICC/AJCC edition. ECE is a more variable and difficult to assess histological feature than LNR, which is therefore possibly more consistent and possibly a superior prognosticator than ECE [ 9 , 47 ]. An important question to address within the frame of prospective multicentric trials would be to assess whether an LNR > 6.5% warrants postoperative chemoradiation, independent of ECE status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Features such as ECE were added in the last UICC/AJCC edition. ECE is a more variable and difficult to assess histological feature than LNR, which is therefore possibly more consistent and possibly a superior prognosticator than ECE [ 9 , 47 ]. An important question to address within the frame of prospective multicentric trials would be to assess whether an LNR > 6.5% warrants postoperative chemoradiation, independent of ECE status.…”
Section: Discussionmentioning
confidence: 99%
“…In case of en bloc resections, non-specified levels are classified as “non-defined”. The standard histopathological diagnosis at our institution has been previously reported [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two studies showed a very high MRI sensitivity of 100% [96% -100%] and 96% [80% -100], respectively, and accounted for 51% of the pooled sample size in the meta-analysis. Our meta-analysis included a recent study from 2020 that found the sensitivity of MRI to be of only 75% [66% -83%], opposing the accuracy of MRI [24].…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…The following variables were retrieved and double-checked in a non-blinded manner by two authors (Galli J, Nisa L): age, initial TNM staging, initial treatment, recurrence TNM staging, details of salvage surgery performed, results of histopathologic neck node analysis from the salvage surgery, postoperative adverse events within 30 days scored according to the Clavien-Dindo classification and long-term sequelae, and status at the time of follow-up [19] . The 7th edition of the UICC classification was used for tumor staging [20] . MRI and PET/CT sequences were acquired as previously described [21,22] .…”
Section: Extraction Of Data and Evaluation Of Imagingmentioning
confidence: 99%